International business : new challenges, new forms, new perspectives - Harris, Simon , 1956-; Kuivalainen, Olli; Stoyanova, Veselina (Academy of International Business series, 2012)
Provides an in-depth analysis of some of the most recent challenges for international businesses, such as corporate social responsibility and the phenomenon of outward foreign direct investment from China. Reflects on the new perspectives in international business by presenting the experience of successful business experts in the field.